2014
DOI: 10.1590/s1984-82502014000400018
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medication use in institutionalized older adults according to the Beers Criteria

Abstract: The need for specific care, coupled with new family arrangements, has contributed to the increasing institutionalization of elderly members. The purpose of this study was to evaluate drug use by institutionalized older adults according to Beers Criteria. This prospective, longitudinal study was conducted in the three non-profit long-stay geriatric care institutions of Campo Grande, in the Central-West region of Brazil. All subjects aged 60 years and above on November 2011 were included and followed until Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(50 reference statements)
0
2
0
3
Order By: Relevance
“…Despite this, 100% of the elder people aged over 80 years old participants of this survey were making use of AAS. A study using as reference the 2012 Beers Criteria found frequency of use of AAS for the elderly ranging between 30 and 80%, in three long-stay institutions (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, 100% of the elder people aged over 80 years old participants of this survey were making use of AAS. A study using as reference the 2012 Beers Criteria found frequency of use of AAS for the elderly ranging between 30 and 80%, in three long-stay institutions (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs were excluded from the former criteria due to lack of scientific evidence or withdrawn from the market (Fick et al, 2015;O'Mahony et al, 2015). It is possible that the use of the revised criteria may reveal higher prevalence of PIMs, as it has been reported in recent Brazilian studies according to 2012 Beers (35.0-51.8%) (Ganassin, Matos, Toffoli-Kadri, 2014;Martins et al, 2015;Oliveira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…É possível observar as três classes de medicamentos mais prescritas, para cada estudo de amostra hospitalar, conforme tabela 6: -Conceição, et al, 2017;Ganassin, et al, 2014;Mauro Cunha Xavier Pinto, et al, 2013;Vieira De Lima, Garbin, Garbin, Sumida, & Saliba, 2013).…”
Section: Descrição Estrita De Buscaunclassified
“…Foi possível observar a maior prevalência de SF em todos os estudos com amostra em ILP, exceto no estudo de Ganassim, et al (2014), com 42,1%. Quanto à prevalência de MPI, esteve entre 63,01% (Pinto, et al, 2013) e 98,7% (Ganassin, et al, 2014), com prevalência de PF de 33,6%, demonstrada apenas no estudo de Alves-Conceição, et al (2017).…”
Section: Descrição Estrita De Buscaunclassified
See 1 more Smart Citation